Crescimento e qualidade dos frutos do meloeiro sob diferentes lâminas de água e doses de potássio fertirrigado com gotejamento subsuperficial - Rocha, Carlos Régis Torquato (2015)
Aimed to evaluate the effect of different depths of water and potassium levels on melon crop under subsurface irrigation by avaluation of growth and fruit. The experiment was conducted during the period February to September 2014, on the Campus Federal Institute of education, science and technology of Ceará -IFCE, on an area of 374,4 m2 (28,8 m x 13,0 m). Was used the statistical design of randomized blocks with 4 repetitions , arranged in factorial scheme of 4 x 4. The treatments resulted from the combination of four irrigation levels and doses of potassium. Drippers Netafim brand were click-type auto compensantes with anti-sucção mechanism tife with flow of 4 L h-1, 0,5 m line spaced with one dripper per plant. The blades were irrigation L1, L2, L3 and L4 (50; 75; 100 125%; often the evaporation class A tank) and potassium levels K1, K2, K3 and K4 (50, 75, 100, 125% of K2O plant-1). Tension monitoring of the water in the soil was done with tensiometers installed around the plant. Morphological variables quantified plant development were: number of leaves, stem diameter, length of main stem and leaf area. Fruit quality parameters were: total soluble solids, longitudinal and transverse diameter, shape index of fruits and fruit mass. The potassium content in the leaves was evaluated with the leaves collected shortly after the harvest of the fruits. At the end of the cycle of culture soil samples were collected at 0-20 cm layer, for the determination of potassium in soil. The largest irrigation depths, as well as the lowest potassium levels up to 65 DAT seedlings provide best vegetative development to culture, when the number of leaves, stem diameter and leaf area. The highest values of SST were obtained by combining the smallest blade of irrigation and greater dose of potassium. Irrigation management with the smallest irrigation blades, as well as the application via the potassium doses smaller fertirrigation until 65 DAT seedling promote the increase in size of the fruit. The spherical shaped fruits (preferred) was obtained with the largest irrigation blade (125% of ETcp). The average mass of the fruits are larger when culture is fertirrigada with the smallest blades of irrigation, and the application of the maximum levels of potassium. The application of smaller irrigation, depths didn't compromise the quality characteristics of the fruit. For the largest irrigation blade resulted in higher concentrations of potassium in soil. The potassium content in leaves increased linearly with the potassium levels and blades of irrigation applied.